2004
DOI: 10.1111/j.0022-202x.2004.22606.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with 5-Fluorouracil and Celecoxib Displays Synergistic Regression of Ultraviolet Light B-Induced Skin Tumors

Abstract: Standard chemotherapeutic agents used for the treatment of pre-cancerous skin lesions and non-melanoma skin cancers are not completely effective. Several studies have suggested that repeated inflammatory sunburn reactions, which include the induction of cyclooxygenase-2 (COX-2) and the subsequent production of prostaglandins, play a role in skin cancer development. COX-2 inhibition has been demonstrated to be a potent means of preventing skin cancer development in mice; however, COX-2 inhibitors alone are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…Celecoxib has been shown to enhance clinically the antitumor eYcacy of doxorubicin (Awara et al 2004) and 5-Xuorouracil (Wilgus et al 2004). In this study, cytostatic eYcacy of doxorubicin was determined by MTT assay in MCF-7 cells, and we found that celecoxib and doxorubicin were synergistic.…”
Section: Discussionmentioning
confidence: 64%
“…Celecoxib has been shown to enhance clinically the antitumor eYcacy of doxorubicin (Awara et al 2004) and 5-Xuorouracil (Wilgus et al 2004). In this study, cytostatic eYcacy of doxorubicin was determined by MTT assay in MCF-7 cells, and we found that celecoxib and doxorubicin were synergistic.…”
Section: Discussionmentioning
confidence: 64%
“…The results of this study suggest that mild Zn supplementation may be helpful for preventing the progression of NMSCs, even in Zn‐sufficient individuals, possibly in combination with other preventive treatments currently under investigation in UV or DMBA/PMA induction models, some showing promise 44, 45, 46, 47, 48, 49. Further studies are needed to define mechanisms that enable dietary Zn supplementation to reduce tumor burdens in Fhit − / − mice, perhaps with a focus on experiments aimed at evaluating differences in responses in male and female mice, since females displayed the most emphatic reductions.…”
Section: Discussionmentioning
confidence: 85%
“…Remarkably, in chronically UV Bchallenged SKH skin the inhibitors are not found to inhibit edema or inflammation [185]. Beside the chemo-preventive effects, celecoxib exhibited therapeutic efficacy inducing a partial regression of UV-induced pre-existing tumors [188,189], an inhibitory effect that can be synergistically enhanced by combination treatments of celecoxib with difluoromethylornithine or 5-fluorouracil [188,190] and an effect that depends on continuous treatment [188]. Beyond stimulation of apoptosis, a further mechanism that could contribute to the antitumorigenic effects of NSAIDs in skin is highlighted recently.…”
Section: Uv Light-induced Carcinogenesis In Mouse Skinmentioning
confidence: 99%